Dynamics of an Anti-competitive Two Dimensional Rational System of Difference Equations - Garić-Demirović, M.; Nurkanović, M. (Sarajevo Journal of Mathematics, 2024)
We investigate the global asymptotic behavior of solutions of the following anti-competitive system of rational difference equations \begin{equation*} x_{n+1}=\frac{γ _{1}y_{n}}{A_{1}+x_{n}}+h,\quad y_{n+1}=\frac{β _{2}x_{n}}{A_{2}+y_{n}},\quad n=0,1,…, \end{equation*} where the parameters $γ _1,β _2,A_{1},A_{2}$ and $h$ are positive numbers and the initial conditions $x_{0},y_{0}$ are arbitrary nonnegative numbers. 2000 Mathematics Subject Classification. 39A10, 39A11